2020
DOI: 10.3390/jcm9010263
|View full text |Cite
|
Sign up to set email alerts
|

Ringer’s Lactate Prevents Early Organ Failure by Providing Extracellular Calcium

Abstract: Objective: Ringer’s lactate may improve early systemic inflammation during critical illnesses like severe acute pancreatitis, which are associated with hypocalcemia. Ringer’s lactate is buffered and contains lactate and calcium. We, thus analyzed extracellular calcium or lactate’s effects on the mechanisms, intermediary markers, and organ failure in models mimicking human disease with nonesterified fatty acid (NEFA) elevation. Methods: Meta-analyses and experimental studies were performed. Experimentally, extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 51 publications
0
29
0
1
Order By: Relevance
“…The salient features linking severe COVID-19 and hypocalcemia are: 4. Unsaturated fatty acids can induce the cytokine storm [5] and multisystem organ failure [2,4] such as noted in COVID-19. 5.…”
Section: To the Editormentioning
confidence: 99%
“…The salient features linking severe COVID-19 and hypocalcemia are: 4. Unsaturated fatty acids can induce the cytokine storm [5] and multisystem organ failure [2,4] such as noted in COVID-19. 5.…”
Section: To the Editormentioning
confidence: 99%
“… 39 , 153 , 154 , 155 Unsaturated fatty acids 40 generated by adipose lipolysis cause MSOF and non-endocrine hypocalcemia, while calcium ameliorates MSOF. 152 , 156 Most recently, it is reported that unsaturated fat intake is associated with increased mortality from COVID-19, and unsaturated fatty acids cause an injury, organ failure resembling COVID-19. 157 As prophylactic calcium and albumin could prevent linoleic acid and induced MSOF in vivo, early supplementation with albumin and calcium can bind unsaturated fatty acids, reduce injury in severe COVID-19 cases.…”
Section: Treatment Of Covid-19mentioning
confidence: 99%
“…Patients severely affected by COVID-19 have higher levels of unbound [ 17 ] and unsaturated fatty acids [ 18 ]. The high levels of unsaturated fatty acids can precipitate a cytokine storm [ 19 ] and also bind calcium, leading to reduced calcium levels [ 20 ]. Furthermore, another study has suggested that lower levels of vitamin D may be associated with more severe COVID infection and therefore a greater likelihood of hypocalcemia [ 21 ].…”
Section: Sars-cov-2 and Hypoparathyroidismmentioning
confidence: 99%